Interaction I / A Reading Skills Book - Hartmann Pamela; Kirn Elaine (Random House, 1985)
College Life, Nature, Living to Eat or Eating to Live?, Getting Around the Community, Housing and the Family, Emergencies and Strange Experiences, Health and Illness, Television and the Media, Friends and Social Life, Customs and Celebrations and Holidays, Recreation, You and the Consumer.